2022
DOI: 10.1002/jmri.28211
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of gliomas grading and IDH status decoding A comparison between 3D amide proton transfer APT and four diffusion‐weighted MRI models

Abstract: Background: The focus of neuro-oncology research has changed from histopathologic grading to molecular characteristics, and medical imaging routinely follows this change. Purpose: To compare the diagnostic performance of amide proton transfer (APT) and four diffusion models in gliomas grading and isocitrate dehydrogenase (IDH) genotype. Study Type: Prospective. Population: A total of 62 participants (37 males, 25 females; mean age, 52 AE 13 years) whose IDH genotypes were mutant in 6 of 14 grade II gliomas, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although several studies have referred to IDH mutation using M.R. spectroscopy, perfusion, permeability, or chemical exchange saturation transfer imaging, using solely one factor may not suffice for non-contrast-enhanced gliomas [32][33][34][35][36][37]. As molecular diagnosis is becoming greatly important in glioma treatment, a versatile and simple method for predicting genetic differences remains warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have referred to IDH mutation using M.R. spectroscopy, perfusion, permeability, or chemical exchange saturation transfer imaging, using solely one factor may not suffice for non-contrast-enhanced gliomas [32][33][34][35][36][37]. As molecular diagnosis is becoming greatly important in glioma treatment, a versatile and simple method for predicting genetic differences remains warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we utilized nested cross-validation to confirm the validity of the predictive model. Second, our study lacked the molecular subtype for the samples, while the molecular phenotype is crucial for the prognosis of glioma ( 49 , 50 ). Future medical imaging research should focus on the molecular characteristics of glioma, which could aid in more accurate subtype prediction and the development of individual treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…11 According to a previous study, ICVF was found to be surprisingly increased in ischemic areas. 33 .91 for ODI). 14 In the study by Guo et al, mean ICVF and ODI were not statistically different in HGG areas compared to LGG, while ISO increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that NODDI was developed for healthy brain tissue is a major limitation 11 . According to a previous study, ICVF was found to be surprisingly increased in ischemic areas 33 . Findings in glioma grading studies related to NODDI are also contradictory.…”
Section: Discussionmentioning
confidence: 99%